Aspirations, inequality, and behavioral change: evidence from Colombia. Issue 1 (31st December 2022) - Edison Rojas Mora, Jaime
ABSTRACT: In this article, I analyze why inequality can discourage investment. I derive my hypothesis from the theory of aspirations as a reference point. A more significant aspiration gap – the distance between the current state and the aspired state – leads to frustration and fewer incentives to invest. In study I, I use data from a longitudinal panel, exploiting environmental shocks to identify a plausibly exogenous source of variation for inequality. I combine it with an indirect measurement of aspirations using data on wealth, computed for the plausible reference group, defined as cells within the population, sharing similar observable characteristics. Finally, I use the variation in the total debt as the outcome variable. In study II, I use data from a specialized survey where shocks and aspirations are directly measured. I look at total debt as the outcome. Although the two tests are only partially conclusive, the evidence aligns with the central hypothesis.